ANALISA PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING CELEBRITY FITNESS CENTER SURABAYA - Peter Kurniawan Ho (Jurnal Strategi Pemasaran, 2017)
The development of fitness centers in the city of Surabaya is growing rapidly, strategic locations such as in the center of the famous city in the city of Surabaya, of course this is directly proportional to the changing lifestyle of people in the city of Surabaya is more advanced and the view of an increasingly healthy lifestyle. With so many fitness centers in Surabaya, this is also affecting the fitness industry competition in terms of quality of service that becomes one factor that impacts on customer satisfaction, which in the end faced with the advantage of improving both the quality and the quantity of output produced. This research aims to analyze the influence of Service Quality (Tangible, Emphaty, Responsiveness, Realibility, Assurance) to Customer Loyalty (Say positive thing, Recommend to friend, Continue purchasing) by considering the factor of Customer Satisfaction (Satisfaction as Fulfillment, Satisfaction as Pleasure, Satisfaction as Ambivalance) This research was conducted by distributing questionnaires to 100 respondents of Celebrity Fitness Centre customers. Analyze technique used is quantitative analysis technique with path analysis method.